2004
DOI: 10.1038/sj.onc.1207394
|View full text |Cite
|
Sign up to set email alerts
|

Cdc25A phosphatase: combinatorial phosphorylation, ubiquitylation and proteolysis

Abstract: In eukaryotic cells, control mechanisms of cell-cycle progression have evolved to accurately monitor the integrity of genetic information to be transferred to the progeny. Cdc25A phosphatase is an essential activator of cell-cycle progression and is targeted by checkpoint signals. Ubiquitylation regulates Cdc25A activity through fine tuning of its protein levels. Two different ubiquitin ligases (APC/C and SCF complex) are involved in Cdc25A turnover. While APC/C is involved in regulating Cdc25A at the exit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
174
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 69 publications
(74 reference statements)
2
174
1
2
Order By: Relevance
“…35 In this study, we show that besides translation inhibition Roc-A induces a rapid degradation of Cdc25A via activation of ATM/ATR-Chk1/Chk2 kinases (Figs. 2c and 2d).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…35 In this study, we show that besides translation inhibition Roc-A induces a rapid degradation of Cdc25A via activation of ATM/ATR-Chk1/Chk2 kinases (Figs. 2c and 2d).…”
Section: Discussionmentioning
confidence: 52%
“…Protein synthesis was estimated by measuring the amount of incorporated 35 S-methionine. Briefly, cells (1 3 10 6 ) were incubated for 3 hr in methionine-free medium followed by adding 7 lCi per well of 35 S-methionine-labeling mix (PerkinElmer, Waltham, MA).…”
Section: Translation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…5 a and 5 b ). The stability of Cdc25A protein is largely regulated by the DNA damage response kinases ATM/ATR‐Chk1/Chk2 34. We show that TC induces a rapid activation of ATM/ATR‐Chk1/Chk2 kinases (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…The APC/C mediates degradation of Cdc25A starting at the end of mitosis throughout the G 1 phase, while the SCF complex plays a critical role in Cdc25A degradation in response to DNA damage. 10,44 Importantly, we found that loss of Importantly, we found that loss of we found that loss of loss of MIF uncouples Chk1/Chk2 checkpoints from proteasomal degradation of Cdc25A under conditions of DNA damage.…”
Section: Mif Is An Essential Component Of the G 2 M Dna Damage Checkpmentioning
confidence: 69%